The Effect of Product Quality, Price, and Halal Certification on The Sales Volume (Literature Review) - Fardani, Nadya (Green Publisher, 2023)
The current globalization phenomenon provides significant opportunities for the development of the national economy. One of the impacts of the globalization phenomenon is the expansion of transactions in the global economy which has an impact on increasing market competition. In responding to this phenomenon, preparation is needed from business owner to increase sales of their products. Therefore, research is needed to determine the factor that affect sales volume. This literature review article is written to build a research hypothesis related to product sales volume that are influenced by product quality, price, and halal certification. The method used in writing the article is a library research method sourced from online media, such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are product quality, price, and halal certification affect product sales volume.